A New Cross-domain Strategy for Safeguarding the Danish Cultural Heritage - Mark, Niels (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
In the spring of 2003, the Danish Ministry of Culture launched a report, which comprised an evaluation of existing strategies for safeguarding the Danish cultural heritage and recommendations for future development. The report is very ambitious and covers all kinds of cultural material in archives, museums and libraries with a national responsibility. Two working committees with members primarily from the national institutions, each headed by the heads of the two departments in the ministry, were set up and given 8 months to produce the report (DMoC, 2003). In this paper I shall shortly inform you of the background for the investigation, the procedures and analyses in the work process, the results, the most important recommendations and finally, the library sector's expectations to future development.